Lost at the Edge of Uncertainty: Measuring Player Uncertainty in Digital Games. Issue 12 (21st July 2019) - Power, Christopher; Cairns, Paul; Denisova, Alena; Papaioannou, Themis; Gultrom, Ruth
ABSTRACT: Uncertainty has previously been identified as an important ingredient of engaging games. Design in games can create different levels of uncertainty in players that they can recognize and describe as being either attributable to external forces, such as chance or hidden information, or internal to their own understanding of what to do in relation to their own goals. While it appears that uncertainty can contribute both positive and negative play experiences, there is little work in trying to operationalize and measure this concept as a component of player experience. Reported in this article is an analysis of data from over 700 players using modern bi-factor analysis techniques resulting in a five factor psychometric scale which captures the broad feelings of players about uncertainty in games. Three of these specific factors appear to point toward a single generic factor of uncertainty that is internal to the players, one captures experiences relating to external uncertainty, with the final factor relating to player's experience of exploring the game to resolve uncertainty. In order to further validate the scale, we conducted an experiment with a commercial puzzle game manipulating the duration of play with predicted outcomes on the different specific factors of the scale. Overall the scale shows promise with good statistical reliability and construct validity of the separate factors and so will be a useful tool for further investigating player experiences in digital games.